Multiple Frequency Ultrasounds Assisted Oil Sands Separation Technology - LIAO, Kaili; GE, Jijiang; ZHANG, Guicai; FU, Lipei (Archives of Acoustics, 2017)
Ultrasound has a wide range of applications in oil sands separation industry due to its green and nopolluting characteristics. The combined ultrasounds technology has been widely used in many industries by virtue of the synergistic effect of cavitation effect; meanwhile, dual-frequency ultrasounds have been reported being used in lotion oil sands technology. Based on this idea, this study focuses on the application of multiple frequency ultrasounds in oil sands separation, and a comparative study has been conducted between the combined ultrasounds systems with the difference in the number of the ultrasound. The results show that the oil production rate of the samples treated by the lotion of sodium dodecyl benzene sulfonate (SDBS) and assisted by multiple frequency ultrasounds (96%) is significantly higher than that of the single frequency ultrasound (76%); the bigger the number of the ultrasound participating in the combination is, the higher the oil production rate of the oil sands is; the lower the frequency of the ultrasounds employed in the combined system is, the higher the oil production rate is. The optimum treating conditions for tri-frequency ultrasounds assisted technology are as follow: the treating time is 10–15 min, the treating temperature is 20–30ºC, the concentration of surfactant in the lotion is 1.5 g/l, and the mass ratio of the lotion to oil sands is 1.8. In short, the use of multiple frequency ultrasounds can improve the oil production rate of oil sands, reduce the energy consumption during the separation process, and reduce the environmental contamination; therefore, multiple frequency ultrasounds assisted oil sands separation technology is a promising technology for oil sands resources exploitation with high efficiency.